Preparation, characterization, dissolution, and permeation of flibanserin − 2-HP-β-cyclodextrin inclusion complexes - Adel F. Alghaith; Gamal M. Mahrous; Diaa Eldin Zidan; Nabil A. Alhakamy; Abdulmohsin J. Alamoudi; Awwad A. Radwan (Elsevier, 2021)
Flibanserin (FLB), an antiserotonin drug, is used to treat women with hypoactive sexual appetite disorder. FLB shows low bioavailability (~33%) probably due to its low water solubility. The current study investigated the impact of hydroxypropyl-β-cyclodextrin (HP-β-CD) and sodium lauryl sulfate (SLS) on the dissolution and permeation of FLB. HP-β-CD-FLB inclusion complexes were prepared using physical mixing and kneading at 1:1 and 1:2 M ratios and characterized using differential scanning calorimetry, Fourier transform infrared spectroscopy, and powder X-ray diffractometry. The dissolution and permeation of the complexes through a cellophane membrane were performed in, 0.1, 0.3 and 0.5% SLS in phosphate buffer (pH 6.8).Derived from the slope of the linear phase solubility diagram, the apparent stability constant (K1:1) was 372.54 M−1. Kneading changed the crystalline form of FLB to an amorphous appearance characterized by minimal crystalline peaks, indicating successful inclusion complex formation. In addition, the HP-β-CD-FLB inclusion complexes showed twofold increased dissolution efficiency at 6 h. The cumulative FLB amount permeated at 6 h increased from 14.1% to 21.88% and 34.56% in the presence of 0.1% and 0.3% of SLS, respectively. However, increasing SLS to 0.5% did not show an increase in FLB permeation. Therefore, the HP-β-CD-FLB inclusion complex has an improved dissolution rate compared to FLB alone. The presence of SLS in the dissolution medium increases the dissolution rate of pure FLB and its complex with HP-β-CD. kneaded 1:1 complex was formulated bioadhesive buccal tablets and showed enhanced drug release.